TRIM16 Promotes Osteogenic Differentiation of Human Periodontal Ligament Stem Cells by Modulating CHIP-Mediated Degradation of RUNX2 - Zhao, Yi; Zhai, Qiaoli; Liu, Hong; Xi, Xun; Chen, Shuai; Liu, Dongxu (Frontiers in Cell and Developmental Biology, 2021)
Bone regeneration is the ultimate goal of periodontal therapies, in which osteogenic differentiation of human periodontal ligament stem cells plays a critical role. The tripartite motif (TRIM)16, an E3 ubiquitin ligase, is downregulated in periodontal tissues of patients with periodontitis, while the role of TRIM16 in the osteogenic differentiation of human periodontal ligament stem cells (hPDLSCs) is largely unknown. Firstly, we found that TRIM16 was increased throughout the osteogenic media induced differentiation of hPDLSCs. Then overexpression plasmids and specific short-hairpin RNAs (shRNAs) were constructed to manipulate the expression of target molecules. TRIM16 significantly promoted alkaline phosphatase activity, mineralized nodule formation, and positively regulated the expression of osteo-specific markers RUNX2, COL1A1 and OCN except the mRNA of RUNX2. Mechanistically, TRIM16 serves as a pivotal factor that stabilizes RUNX2 protein levels by decreasing CHIP-mediated K48-linked ubiquitination degradation of the RUNX2 protein. This study identified a novel mechanism of TRIM16 in regulating stability of the RUNX2 protein, which promoted the osteogenic differentiation of hPDLSCs. TRIM16 may be a potential target of stem cell based-bone regeneration for periodontal therapies.